Minimum Linear Arrangement of Series-Parallel Graphs - Scheideler, Christian; Eikel, Martina; Setzer, Alexander (Proceedings of the 12th Workshop on Approximation and Online Algorithms (WAOA))
We present a factor $14D^2$ approximation algorithm for the minimum linear arrangement problem on series-parallel graphs, where $D$ is the maximum degree in the graph. Given a suitable decomposition of the graph, our algorithm runs in time $O(|E|)$ and is very easy to implement. Its divide-and-conquer approach allows for an effective parallelization. Note that a suitable decomposition can also be computed in time $O(|E|\log{|E|})$ (or even $O(\log{|E|}\log^*{|E|})$ on an EREW PRAM using $O(|E|)$ processors). For the proof of the approximation ratio, we use a sophisticated charging method that uses techniques similar to amortized analysis in advanced data structures. On general graphs, the minimum linear arrangement problem is known to be NP-hard. To the best of our knowledge, the minimum linear arrangement problem on series-parallel graphs has not been studied before.

HSkip+: A Self-Stabilizing Overlay Network for Nodes with Heterogeneous Bandwidths - Feldotto, Matthias; Scheideler, Christian; Graffi, Kalman (Proceedings of the 14th IEEE International Conference on Peer-to-Peer Computing (P2P))
In this paper we present and analyze HSkip+, a self-stabilizing overlay network for nodes with arbitrary heterogeneous bandwidths. HSkip+ has the same topology as the Skip+ graph proposed by Jacob et al. [PODC 2009] but its self-stabilization mechanism significantly outperforms the self-stabilization mechanism proposed for Skip+. Also, the nodes are now ordered according to their bandwidths and not according to their identifiers. Various other solutions have already been proposed for overlay networks with heterogeneous bandwidths, but they are not self-stabilizing. In addition to HSkip+ being self-stabilizing, its performance is on par with the best previous bounds on the time and work for joining or leaving a network of peers of logarithmic diameter and degree and arbitrary bandwidths. Also, the dilation and congestion for routing messages is on par with the best previous bounds for such networks, so that HSkip+ combines the advantages of both worlds. Our theoretical investigations are backed by simulations demonstrating that HSkip+ is indeed performing much better than Skip+ and working correctly under high churn rates.

Competitive throughput in multi-hop wireless networks despite adaptive jamming - W. Richa, Andréa; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Distributed Computing)

Corona: A stabilizing deterministic message-passing skip list - Mohd Nor, Rizal; Nesterenko, Mikhail; Scheideler, Christian (Theor. Comput. Sci.)

An Efficient and Fair MAC Protocol Robust to Reactive Interference - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (IEEE/ACM Trans. Netw.)

Cliquenbildung in verteilten Systemen - Blumentritt, Fritz

Towards Duality of Multicommodity Multiroute Cuts and Flows: Multilevel Ball-Growing - Kolman, Petr; Scheideler, Christian (Theory of Computing Systems)
An elementary h-route ow, for an integer h 1, is a set of h edge- disjoint paths between a source and a sink, each path carrying a unit of ow, and an h-route ow is a non-negative linear combination of elementary h-routeows. An h-route cut is a set of edges whose removal decreases the maximum h-route ow between a given source-sink pair (or between every source-sink pair in the multicommodity setting) to zero. The main result of this paper is an approximate duality theorem for multicommodity h-route cuts and ows, for h 3: The size of a minimum h-route cut is at least f=h and at most O(log4 k f) where f is the size of the maximum h-routeow and k is the number of commodities. The main step towards the proof of this duality is the design and analysis of a polynomial-time approximation algorithm for the minimum h-route cut problem for h = 3 that has an approximation ratio of O(log4 k). Previously, polylogarithmic approximation was known only for h-route cuts for h 2. A key ingredient of our algorithm is a novel rounding technique that we call multilevel ball-growing. Though the proof of the duality relies on this algorithm, it is not a straightforward corollary of it as in the case of classical multicommodity ows and cuts. Similar results are shown also for the sparsest multiroute cut problem.

Symbiotic Coupling of P2P and Cloud Systems: The Wikipedia Case - Graffi, Kalman; Bremer, Lars (Proceedings of the International Conference on Communications (ICC'13))
Cloud computing offers high availability, dynamic scalability, and elasticity requiring only very little administration. However, this service comes with financial costs. Peer-to-peer systems, in contrast, operate at very low costs but cannot match the quality of service of the cloud. This paper focuses on the case study of Wikipedia and presents an approach to reduce the operational costs of hosting similar websites in the cloud by using a practical peer-to-peer approach. The visitors of the site are joining a Chord overlay, which acts as first cache for article lookups. Simulation results show, that up to 72% of the article lookups in Wikipedia could be answered by other visitors instead of using the cloud.

Locally Self-Adjusting Tree Networks - Avin, Chen; Häupler, Bernhard; Lotker, Zvi; Scheideler, Christian; Schmid, Stefan (Proceedings of the 27th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
This paper initiates the study of self-adjusting networks (or distributed data structures) whose topologies dynamically adapt to a communication pattern $σ$. We present a fully decentralized self-adjusting solution called SplayNet. A SplayNet is a distributed generalization of the classic splay tree concept. It ensures short paths (which can be found using local-greedy routing) between communication partners while minimizing topological rearrangements. We derive an upper bound for the amortized communication cost of a SplayNet based on empirical entropies of $σ$, and show that SplayNets have several interesting convergence properties. For instance, SplayNets features a provable online optimality under special requests scenarios. We also investigate the optimal static network and prove different lower bounds for the average communication cost based on graph cuts and on the empirical entropy of the communication pattern $σ$. From these lower bounds it follows, e.g., that SplayNets are optimal in scenarios where the requests follow a product distribution as well. Finally, this paper shows that in contrast to the Minimum Linear Arrangement problem which is generally NP-hard, the optimal static tree network can be computed in polynomial time for any guest graph, despite the exponentially large graph family. We complement our formal analysis with a small simulation study on a Facebook graph.

IRIS: A Robust Information System Against Insider DoS-Attacks - Eikel, Martina; Scheideler, Christian (Proceedings of the 25th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
In this work we present the first scalable distributed information system,i.e., a system with low storage overhead, that is provably robust againstDenial-of-Service (DoS) attacks by a current insider. We allow acurrent insider to have complete knowledge about the information systemand to have the power to block any ε-fraction of its serversby a DoS-attack, where ε can be chosen up to a constant. The taskof the system is to serve any collection of lookup requests with at most oneper non-blocked server in an efficient way despite this attack. Previously,scalable solutions were only known for DoS-attacks of past insiders, where apast insider only has complete knowledge about some past time pointt_0 of the information system. Scheideler et al. (DISC 2007, SPAA 2009) showedthat in this case it is possible to design an information system so that anyinformation that was inserted or last updated after t_0 is safe against a DoS-attack. But their constructions would not work at all for a current insider. The key idea behindour IRIS system is to make extensive use of coding. More precisely, we presenttwo alternative distributed coding strategies with an at most logarithmicstorage overhead that can handle up to a constant fraction of blocked servers.

HSkip+: A Self-Stabilizing Overlay Network for Nodes with Heterogeneous Bandwidths - Feldotto, Matthias

Continuous Gossip-based Aggregation through Dynamic Information Aging - Graffi, Kalman; Rapp, Vitaly (Proceedings of the International Conference on Computer Communications and Networks (ICCCN'13))
Existing solutions for gossip-based aggregation in peer-to-peer networks use epochs to calculate a global estimation from an initial static set of local values. Once the estimation converges system-wide, a new epoch is started with fresh initial values. Long epochs result in precise estimations based on old measurements and short epochs result in imprecise aggregated estimations. In contrast to this approach, we present in this paper a continuous, epoch-less approach which considers fresh local values in every round of the gossip-based aggregation. By using an approach for dynamic information aging, inaccurate values and values from left peers fade from the aggregation memory. Evaluation shows that the presented approach for continuous information aggregation in peer-to-peer systems monitors the system performance precisely, adapts to changes and is lightweight to operate.

CONE-DHT: A distributed self-stabilizing algorithm for a heterogeneous storage system - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 27th International Symposium on Distributed Computing (DISC))
We consider the problem of managing a dynamic heterogeneous storagesystem in a distributed way so that the amount of data assigned to a hostin that system is related to its capacity. Two central problems have to be solvedfor this: (1) organizing the hosts in an overlay network with low degree and diameterso that one can efficiently check the correct distribution of the data androute between any two hosts, and (2) distributing the data among the hosts so thatthe distribution respects the capacities of the hosts and can easily be adapted asthe set of hosts or their capacities change. We present distributed protocols forthese problems that are self-stabilizing and that do not need any global knowledgeabout the system such as the number of nodes or the overall capacity of thesystem. Prior to this work no solution was known satisfying these properties.

Comparative Evaluation of Peer-to-Peer Systems Using PeerfactSim.KOM - Feldotto, Matthias; Graffi, Kalman (Proceedings of the International Conference on High Performance Computing and Simulation (HPCS'13))
Comparative evaluations of peer-to-peer protocols through simulations are a viable approach to judge the performance and costs of the individual protocols in large-scale networks. In order to support this work, we enhanced the peer-to-peer systems simulator PeerfactSim.KOM with a fine-grained analyzer concept, with exhaustive automated measurements and gnuplot generators as well as a coordination control to evaluate a set of experiment setups in parallel. Thus, by configuring all experiments and protocols only once and starting the simulator, all desired measurements are performed, analyzed, evaluated and combined, resulting in a holistic environment for the comparative evaluation of peer-to-peer systems.

Ca-Re-Chord: A Churn Resistant Self-stabilizing Chord Overlay Network - Graffi, Kalman; Benter, Markus; Divband, Mohammad; Kniesburges, Sebastian; Koutsopoulos, Andreas (Proceedings of the Conference on Networked Systems (NetSys))
Self-stabilization is the property of a system to transfer itself regardless of the initial state into a legitimate state. Chord as a simple, decentralized and scalable distributed hash table is an ideal showcase to introduce self-stabilization for p2p overlays. In this paper, we present Re-Chord, a self-stabilizing version of Chord. We show, that the stabilization process is functional, but prone to strong churn. For that, we present Ca-Re-Chord, a churn resistant version of Re-Chord, that allows the creation of a useful DHT in any kind of graph regardless of the initial state. Simulation results attest the churn resistance and good performance of Ca-Re-Chord.

Bootstrapping Skynet: Calibration and Autonomic Self-Control of Structured Peer-to-Peer Networks - Graffi, Kalman; Klerx, Timo (Proceedings of the International Conference on Peer-to-Peer Computing (P2P'13))
Peer-to-peer systems scale to millions of nodes and provide routing and storage functions with best effort quality. In order to provide a guaranteed quality of the overlay functions, even under strong dynamics in the network with regard to peer capacities, online participation and usage patterns, we propose to calibrate the peer-to-peer overlay and to autonomously learn which qualities can be reached. For that, we simulate the peer-to-peer overlay systematically under a wide range of parameter configurations and use neural networks to learn the effects of the configurations on the quality metrics. Thus, by choosing a specific quality setting by the overlay operator, the network can tune itself to the learned parameter configurations that lead to the desired quality. Evaluation shows that the presented self-calibration succeeds in learning the configuration-quality interdependencies and that peer-to-peer systems can learn and adapt their behavior according to desired quality goals.

Approximation Algorithms for the Linear Arrangement of Special Classes of Graphs - Setzer, Alexander

Adding Capacity-Aware Storage Indirection to Homogeneous Distributed Hash Tables - Wette, Philip; Graffi, Kalman (Proceedings of the Conference on Networked Systems (NetSys))
Distributed hash tables are very versatile to use, as distributed storage is a desirable feature for various applications. Typical structured overlays like Chord, Pastry or Kademlia consider only homogeneous nodes with equal capacities, which does not resemble reality. In a practical use case, nodes might get overloaded by storing popular data. In this paper, we present a general approach to enable capacity awareness and load-balancing capability of homogeneous structured overlays. We introduce a hierarchical second structured overlay aside, which allows efficient capacity-based access on the nodes in the system as hosting mirrors. Simulation results show that the structured overlay is able to store various contents, such as of a social network, with only a negligible number of overloaded peers. Content, even if very popular, is hosted by easily findable capable peers. Thus, long-existing and well-evaluated overlays like Chord or Pastry can be used to create attractive DHT-based applications.

A Deterministic Worst-Case Message Complexity Optimal Solution for Resource Discovery - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of 20th International Colloqium on Structural Information and Communication Complexity (SIROCCO))
We consider the problem of resource discovery in distributed systems. In particular we give an algorithm, such that each node in a network discovers the add ress of any other node in the network. We model the knowledge of the nodes as a virtual overlay network given by a directed graph such that complete knowledge of all nodes corresponds to a complete graph in the overlay network. Although there are several solutions for resource discovery, our solution is the first that achieves worst-case optimal work for each node, i.e. the number of addresses (O(n)) or bits (O(nlogn)) a node receives or sendscoincides with the lower bound, while ensuring only a linearruntime (O(n)) on the number of rounds.

Editorial for Algorithmic Aspects of Wireless Sensor Networks - Dolev, Shlomi; Scheideler, Christian (Theor. Comput. Sci.)

Selfish Distributed Optimization - Monien, Burkhard; Scheideler, Christian (Euro-Par 2012 Parallel Processing - 18th International Conference, Euro-Par 2012, Rhodes Island, Greece, August 27-31, 2012. Proceedings)

Jamming-resistente MAC-Protokolle - Meith, Frank Ingo

Towards higher-dimensional topological self-stabilization: A distributed algorithm for Delaunay graphs - Jacob, Riko; Ritscher, Stephan; Scheideler, Christian; Schmid, Stefan (Theoretical Computer Science)
This article studies the construction of self-stabilizing topologies for distributed systems. While recent research has focused on chain topologies where nodes need to be linearized with respect to their identiers, we explore a natural and relevant 2-dimensional generalization. In particular, we present a local self-stabilizing algorithm DStab which is based on the concept of \local Delaunay graphs" and which forwards temporary edges in greedy fashion reminiscent of compass routing. DStab constructs a Delaunay graph from any initial connected topology and in a distributed manner in time O(n3) in the worst-case; if the initial network contains the Delaunay graph, the convergence time is only O(n) rounds. DStab also ensures that individual node joins and leaves aect a small part of the network only. Such self-stabilizing Delaunay networks have interesting applications and our construction gives insights into the necessary geometric reasoning that is required for higherdimensional linearization problems.Keywords: Distributed Algorithms, Topology Control, Social Networks

Tiara: A self-stabilizing deterministic skip list and skip graph - Clouser, Thomas; Nesterenko, Mikhail; Scheideler, Christian (Theoretical Computer Science)
We present Tiara — a self-stabilizing peer-to-peer network maintenance algorithm. Tiara is truly deterministic which allows it to achieve exact performance bounds. Tiara allows logarithmic searches and topology updates. It is based on a novel sparse 0-1 skip list. We then describe its extension to a ringed structure and to a skip-graph.Key words: Peer-to-peer networks, overlay networks, self-stabilization.

Stabilization, Safety, and Security of Distributed Systems
SSS is an international forum for researchers and practitioners in the design and development of distributed systems with self-properties: (classical) self-stabilizing, self-configuring, self-organizing, self-managing, self-repairing, self-healing, self-optimizing, self-adaptive, and self-protecting. Research in distributed systems is now at a crucialpoint in its evolution, marked by the importance of dynamic systems such as peer-to-peer networks, large-scale wireless sensor networks, mobile ad hoc networks, cloud computing, robotic networks, etc. Moreover, new applications such as grid and web services, banking and e-commerce, e-health and robotics, aerospace and avionics, automotive, industrial process control, etc. have joined the traditional applications of distributed systems. The theory of self-stabilization has been enriched in the last 30 years by high quality research contributions in the areas of algorithmic techniques, formal methodologies, model theoretic issues, and composition techniques. All these areas are essential to the understanding and maintenance of self-properties in fault-tolerant distributed systems.

Smoothed analysis of left-to-right maxima with applications - Damerow, Valentina; Manthey, Bodo; Meyer auf der Heide, Friedhelm; Räcke, Harald; Scheideler, Christian; Sohler, Christian; Tantau, Till (Transactions on Algorithms)
A left-to-right maximum in a sequence of n numbers s_1, …, s_n is a number that is strictly larger than all preceding numbers. In this article we present a smoothed analysis of the number of left-to-right maxima in the presence of additive random noise. We show that for every sequence of n numbers s_i ∈ [0,1] that are perturbed by uniform noise from the interval [-ε,ε], the expected number of left-to-right maxima is Θ(&sqrt;n/ε + log n) for ε>1/n. For Gaussian noise with standard deviation σ we obtain a bound of O((log3/2 n)/σ + log n).We apply our results to the analysis of the smoothed height of binary search trees and the smoothed number of comparisons in the quicksort algorithm and prove bounds of Θ(&sqrt;n/ε + log n) and Θ(n/ε+1&sqrt;n/ε + n log n), respectively, for uniform random noise from the interval [-ε,ε]. Our results can also be applied to bound the smoothed number of points on a convex hull of points in the two-dimensional plane and to smoothed motion complexity, a concept we describe in this article. We bound how often one needs to update a data structure storing the smallest axis-aligned box enclosing a set of points moving in d-dimensional space.

Self-Organizing Particle Systems - Drees, Maximilian; Hüllmann (married name: Eikel), Martina; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 26th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
Nanoparticles are getting more and more in the focus of the scientic community since the potential for the development of very small particles interacting with each other and completing medical and other tasks is getting bigger year by year. In this work we introduce a distributed local algorithm for arranging a set of nanoparticles on the discrete plane into specic geometric shapes, for instance a rectangle. The concept of a particle we use can be seen as a simple mobile robot with the following restrictions: it can only view the state of robots it is physically connected to, is anonymous, has only a constant size memory, can only move by using other particles as an anchor point on which it pulls itself alongside, and it operates in Look-Compute-Move cycles. The main result of this work is the presentation of a random distributed local algorithm which transforms any given connected set of particles into a particular geometric shape. As an example we provide a version of this algorithm for forming a rectangle with an arbitrary predened aspect ratio. To the best of our knowledge this is the rst work that considers arrangement problems for these types of robots.

Self-Optimizing Binary Search Trees - A Game Theoretic Approach - Strothmann, Thim Frederik

Competitive and fair throughput for co-existing networks under adversarial interference - Richa, Andrea W.; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Proceedings of the 31st Annual ACM SIGACT-SIGOPS Symposium on Principles and Distributed Computing (PODC))
This paper initiates the formal study of a fundamental problem: How to efficiently allocate a shared communication medium among a set of K co-existing networks in the presence of arbitrary external interference? While most literature on medium access focuses on how to share a medium among nodes, these approaches are often either not directly applicable to co-existing networks as they would violate the independence requirement, or they yield a low throughput if applied to multiple networks. We present the randomized medium access (MAC) protocol COMAC which guarantees that a given communication channel is shared fairly among competing and independent networks, and that the available bandwidth is used efficiently. These performance guarantees hold in the presence of arbitrary external interference or even under adversarial jamming. Concretely, we show that the co-existing networks can use a Ω(ε2 min{ε, 1/poly(K)})-fraction of the non-jammed time steps for successful message transmissions, where ε is the (arbitrarily distributed) fraction of time which is not jammed.

Brief Announcement: SplayNets - Towards Self-Adjusting Distributed Data Structures - Schmid, Stefan; Avin, Chen; Scheideler, Christian; Häupler, Bernhard; Lotker, Zvi (Proceedings of the 26th International Symposium on Distributed Computing (DISC))
This paper initiates the study of self-adjusting distributed data structures for networks. In particular, we present SplayNets: a binary search tree based network that is self-adjusting to routing request.We derive entropy bounds on the amortized routing cost and show that our splaying algorithm has some interesting properties.

Brief Announcement: Hashed Predecessor Patricia Trie - A Data Structure for Efficient Predecessor Queries in Peer-to-Peer Systems - Kniesburges, Sebastian; Scheideler, Christian (Proceedings of the 26th International Symposium on Distributed Computing (DISC))
The design of ecient search structures for peer-to-peer systems has attracted a lot of attention in recent years. In this announcement we address the problem of nding the predecessor in a key set and present an ecient data structure called hashed Predecessor Patricia trie. Our hashed Predecessor Patricia trie supports PredecessorSearch(x) and Insert(x) and Delete(x) in O(log log u) hash table accesses when u is the size of the universe of the keys. That is the costs only depend on u and not the size of the data structure. One feature of our approach is that it only uses the lookup interface of the hash table and therefore hash table accesses may be realized by any distributed hash table (DHT).

Basic Network Creation Games with Communication Interests - Cord-Landwehr, Andreas; Huellmann (married name: Eikel), Martina; Kling, Peter; Setzer, Alexander (Proceedings of the 5th International Symposium on Algorithmic Game Theory (SAGT))
Network creation games model the creation and usage costs of networks formed by a set of selfish peers.Each peer has the ability to change the network in a limited way, e.g., by creating or deleting incident links.In doing so, a peer can reduce its individual communication cost.Typically, these costs are modeled by the maximum or average distance in the network.We introduce a generalized version of the basic network creation game (BNCG).In the BNCG (by Alon et al., SPAA 2010), each peer may replace one of its incident links by a link to an arbitrary peer.This is done in a selfish way in order to minimize either the maximum or average distance to all other peers.That is, each peer works towards a network structure that allows himself to communicate efficiently with all other peers.However, participants of large networks are seldom interested in all peers.Rather, they want to communicate efficiently with a small subset only.Our model incorporates these (communication) interests explicitly.Given peers with interests and a communication network forming a tree, we prove several results on the structure and quality of equilibria in our model.We focus on the MAX-version, i.e., each node tries to minimize the maximum distance to nodes it is interested in, and give an upper bound of O(\sqrt(n)) for the private costs in an equilibrium of n peers.Moreover, we give an equilibrium for a circular interest graph where a node has private cost Omega(\sqrt(n)), showing that our bound is tight.This example can be extended such that we get a tight bound of Theta(\sqrt(n)) for the price of anarchy.For the case of general networks we show the price of anarchy to be Theta(n).Additionally, we prove an interesting connection between a maximum independent set in the interest graph and the private costs of the peers.

Approximate Duality of Multicommodity Multiroute Flows and Cuts: Single Source Case - Kolman, Petr; Scheideler, Christian (Proceedings of the 23th ACM SIAM Symposium on Discrete Algorithms (SODA))
Given an integer h, a graph G = (V;E) with arbitrary positive edge capacities and k pairs of vertices (s1; t1); (s2; t2); : : : ; (sk; tk), called terminals, an h-route cut is a set F µ E of edges such that after the removal of the edges in F no pair si ¡ ti is connected by h edge-disjoint paths (i.e., the connectivity of every si ¡ ti pair is at most h ¡ 1 in (V;E n F)). The h-route cut is a natural generalization of the classical cut problem for multicommodity °ows (take h = 1). The main result of this paper is an O(h722h log2 k)-approximation algorithm for the minimum h-route cut problem in the case that s1 = s2 = ¢ ¢ ¢ = sk, called the single source case. As a corollary of it we obtain an approximate duality theorem for multiroute multicom-modity °ows and cuts with a single source. This partially answers an open question posted in several previous papers dealing with cuts for multicommodity multiroute problems.

A Self-Stabilization Process for Small-World Networks - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 26th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
Small-world networks have received significant attention because of their potential as models for the interaction networks of complex systems. Specifically, neither random networks nor regular lattices seem to be an adequate framework within which to study real-world complex systems such as chemical-reaction networks, neural networks, food webs, social networks, scientific-collaboration networks, and computer networks. Small-world networks provide some desired properties like an expected polylogarithmic distance between two processes in the network, which allows routing in polylogarithmic hops by simple greedy routing, and robustness against attacks or failures. By these properties, small-world networks are possible solutions for large overlay networks comparable to structured overlay networks like CAN, Pastry, Chord, which also provide polylogarithmic routing, but due to their uniform structure, structured overlay networks are more vulnerable to attacks or failures. In this paper we bring together a randomized process converging to a small-world network and a self-stabilization process so that a small-world network is formed out of any weakly connected initial state. To the best of our knowledge this is the first distributed self-stabilization process for building a small-world network.

Competitive and Fair Medium Access Despite Reactive Jamming - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (2011 International Conference on Distributed Computing Systems, ICDCS 2011, Minneapolis, Minnesota, USA, June 20-24, 2011)

Towards jamming-resistant and competitive medium access in the SINR model - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Proceedings of the 3rd ACM workshop on Wireless of the students, by the students, for the students, S3@MOBICOM 2011, Las Vegas, NV, USA, September 19 - 23, 2011)

Self-stabilizing leader election for single-hop wireless networks despite jamming - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Proceedings of the 12th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2011, Paris, France, May 16-20, 2011)

Re-Chord: a self-stabilizing chord overlay network - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (SPAA 2011: Proceedings of the 23rd Annual ACM Symposium on Parallelism in Algorithms and Architectures, San Jose, CA, USA, June 4-6, 2011 (Co-located with FCRC 2011))

Hashed Patricia Trie: Efficient Longest Prefix Matching in Peer-to-Peer Systems - Kniesburges, Sebastian; Scheideler, Christian (WALCOM: Algorithms and Computation - 5th International Workshop, WALCOM 2011, New Delhi, India, February 18-20, 2011. Proceedings)

Programming for Distributed Computing: From Physical to Logical Networks - Scheideler, Christian; Graffi, Kalman (Computer Science, The Hardware, Software and Heart of It)

Broadcasting - How Can I Quickly Disseminate Information? - Scheideler, Christian (Algorithms Unplugged)

Algorithms Unplugged - Vöcking, Berthold; Alt, Helmut; Dietzfelbinger, Martin; Reischuk, Rüdiger; Scheideler, Christian; Vollmer, Heribert; Wagner, Dorothea

Towards Duality of Multicommodity Multiroute Cuts and Flows: Multilevel Ball-Growing - Kolman, Petr; Scheideler, Christian (28th International Symposium on Theoretical Aspects of Computer Science, STACS 2011, March 10-12, 2011, Dortmund, Germany)

Lokale Online-Strategien zur linearen Anordnung von Teilnehmern in einem Peer-to-Peer Netzwerk - Setzer, Alexander

Implementierung eines Verfahrens zur Lösung des 3-Mincut-Problems - Sascha, Brauer

Stabilizing consensus with the power of two choices - Doerr, Benjamin; Goldberg, Leslie Ann; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Proceedings of the 23rd ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
In the standard consensus problem there are n processes with possibly di®erent input values and the goal is to eventually reach a point at which all processes commit to exactly one of these values. We are studying a slight variant of the consensus problem called the stabilizing consensus problem [2]. In this problem, we do not require that each process commits to a ¯nal value at some point, but that eventually they arrive at a common, stable value without necessarily being aware of that. This should work irrespective of the states in which the processes are starting. Our main result is a simple randomized algorithm called median rule that, with high probability, just needs O(logmlog log n + log n) time and work per process to arrive at an almost stable consensus for any set of m legal values as long as an adversary can corrupt the states of at most p n processes at any time. Without adversarial involvement, just O(log n) time and work is needed for a stable consensus, with high probability. As a by-product, we obtain a simple distributed algorithm for approximating the median of n numbers in time O(logmlog log n + log n) under adversarial presence.

Self-Stabilizing DeBruijn Networks - Richa, Andrea W.; Scheideler, Christian (Proceedings of the 13th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
This paper presents a dynamic overlay network based on the De Bruijn graph which we call Linearized De Bruijn (LDB) network. The LDB network has the advantage that it has a guaranteed constant node degree and that the routing between any two nodes takes at most O(log n) hops with high probability. Also, we show that there is a simple local-control algorithm that can recover the LDB network from any network topology that is weakly connected.

Robust Distributed Computation in Dynamic Networks - Brandes, Philipp

PeerfactSim.KOM: A PSP System Simulator - Experiences and Lessons Learned - Graffi, Kalman (Proceedings of the IEEE International Conference on Peer-to-Peer Computing (IEEE PsP))
Research on peer-to-peer (p2p) and distributed systems needs evaluation tools to predict and observe the behavior of protocols and mechanisms in large scale networks. PeerfactSim.KOM is a simulator for large scale distributed/p2p systems aiming at the evaluation of interdependencies in multi-layered p2p systems. The simulator is written in Java, is event-based and mainly used in p2p research projects. The main development of PeerfactSim.KOM started in 2005 and is driven since 2006 by the project “QuaP2P”,which aims at the systematic improvement and benchmarking of p2p systems. Further users of the simulator are working in the project “On-the-ﬂy Computing” aiming at researching p2p-based service oriented architectures. Both projects state severe requirements on the evaluation of multi-layered and large-scale distributed systems. We describe the architecture of PeerfactSim.KOM supporting these requirements in Section II, present the workﬂow, selected experiences and lessons learned in Section III and conclude the overview in Section IV.

Corona: A Stabilizing Deterministic Message-Passing Skip List - Nesterenko, Mikhail; Mohd, Rizal; Scheideler, Christian (Proceedings of the 13th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
We present Corona, a deterministic self-stabilizing algorithm for skip list construction in structured overlay networks. Corona operates in the low-atomicity message-passing asynchronous system model. Corona requires constant process memory space for its operation and, therefore, scales well. We prove the general necessary conditions limiting the initial states from which a self-stabilizing structured overlay network in message-passing system can be constructed. The conditions require that initial state information has to form a weakly connected graph and it should only contain identiers that are present in the system. We formally describe Corona and rigorously prove that it stabilizes from an arbitrary initial state subject to the necessary conditions. We extend Corona to construct a skip graph.

Adaptives Loadbalancing für strukturierte Peer-to-Peer-Netzwerke am Beispiel von Chord - Wette, Philip

Algorithmische Grundlagen verteilter Speichersysteme - Meyer auf der Heide, Friedhelm; Scheideler, Christian (Informatik Spektrum)

Foreword - Gavoille, Cyril; Patt-Shamir, Boaz; Scheideler, Christian (Theory of Computing Systems)

Time Complexity of Distributed Topological Self-stabilization: The Case of Graph Linearization - Gall, Dominik; Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (LATIN 2010: Theoretical Informatics, 9th Latin American Symposium, Oaxaca, Mexico, April 19-23, 2010. Proceedings)

Brief announcement: towards robust medium access in multi-hop networks - Richa, Andrea W.; Zhang, Jin; Scheideler, Christian; Schmid, Stefan (Proceedings of the 29th Annual ACM Symposium on Principles of Distributed Computing, PODC 2010, Zurich, Switzerland, July 25-28, 2010)

A Jamming-Resistant MAC Protocol for Multi-Hop Wireless Networks - Richa, Andrea W.; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Distributed Computing, 24th International Symposium, DISC 2010, Cambridge, MA, USA, September 13-15, 2010. Proceedings)

Brief Announcement: Stabilizing Consensus with the Power of Two Choices - Doerr, Benjamin; Ann Goldberg, Leslie; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Distributed Computing, 24th International Symposium, DISC 2010, Cambridge, MA, USA, September 13-15, 2010. Proceedings)

Algorithms for Sensor Systems - 6th International Workshop on Algorithms for Sensor Systems, Wireless Ad Hoc Networks, and Autonomous Mobile Entities, ALGOSENSORS 2010, Bordeaux, France, July 5, 2010, Revised Selected Papers

Foreword - D. Kleinberg, Robert; Scheideler, Christian (Theory Comput. Syst.)

Towards a Scalable and Robust DHT - Awerbuch, Baruch; Scheideler, Christian (Theory Comput. Syst.)

Robust random number generation for peer-to-peer systems - Awerbuch, Baruch; Scheideler, Christian (Theor. Comput. Sci.)

A Distributed and Oblivious Heap - Scheideler, Christian; Schmid, Stefan (Automata, Languages and Programming, 36th Internatilonal Colloquium, ICALP 2009, Rhodes, Greece, July 5-12, 2009, Proceedings, Part II)

A Self-stabilizing and Local Delaunay Graph Construction - Jacob, Riko; Ritscher, Stephan; Scheideler, Christian; Schmid, Stefan (Algorithms and Computation, 20th International Symposium, ISAAC 2009, Honolulu, Hawaii, USA, December 16-18, 2009. Proceedings)

A distributed polylogarithmic time algorithm for self-stabilizing skip graphs - Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (Proceedings of the 28th Annual ACM Symposium on Principles of Distributed Computing, PODC 2009, Calgary, Alberta, Canada, August 10-12, 2009)

A DoS-resilient information system for dynamic data management - Baumgart, Matthias; Scheideler, Christian; Schmid, Stefan (SPAA 2009: Proceedings of the 21st Annual ACM Symposium on Parallelism in Algorithms and Architectures, Calgary, Alberta, Canada, August 11-13, 2009)

Brief Announcement: On the Time Complexity of Distributed Topological Self-stabilization - Gall, Dominik; Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (Stabilization, Safety, and Security of Distributed Systems, 11th International Symposium, SSS 2009, Lyon, France, November 3-6, 2009. Proceedings)

Stabilizing Consensus with the Power of Two Choices - Doerr, Benjamin; Ann Goldberg, Leslie; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Algorithmic Methods for Distributed Cooperative Systems, 06.09. - 11.09.2009)

An O(log n) dominating set protocol for wireless ad-hoc networks under the physical interference model - Scheideler, Christian; W. Richa, Andréa; Santi, Paolo (Proceedings of the 9th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2008, Hong Kong, China, May 26-30, 2008)

Algorithms for Overlay Networks - Scheideler, Christian (Bulletin of the EATCS)

A jamming-resistant MAC protocol for single-hop wireless networks - Awerbuch, Baruch; W. Richa, Andréa; Scheideler, Christian (Proceedings of the Twenty-Seventh Annual ACM Symposium on Principles of Distributed Computing, PODC 2008, Toronto, Canada, August 18-21, 2008)

SPREAD: an adaptive scheme for redundant and fair storage in dynamic heterogeneous storage systems - Mense, Mario; Scheideler, Christian (Proceedings of the Nineteenth Annual ACM-SIAM Symposium on Discrete Algorithms, SODA 2008, San Francisco, California, USA, January 20-22, 2008)

Tiara: A Self-stabilizing Deterministic Skip List - Clouser, Thomas; Nesterenko, Mikhail; Scheideler, Christian (Stabilization, Safety, and Security of Distributed Systems, 10th International Symposium, SSS 2008, Detroit, MI, USA, November 21-23, 2008. Proceedings)

Broadcasting: Wie verbreite ich schnell Informationen? - Scheideler, Christian (Taschenbuch der Algorithmen)

INFORMATIK 2008, Beherrschbare Systeme - dank Informatik, Band 1, Beiträge der 38. Jahrestagung der Gesellschaft für Informatik e.V. (GI), 8. - 13. September, in München, Deutschland

Taschenbuch der Algorithmen - Vöcking, Berthold; Alt, Helmut; Dietzfelbinger, Martin; Reischuk, Rüdiger; Scheideler, Christian; Vollmer, Heribert; Wagner, Dorothea

Algorithms for Fault-Tolerant Routing in Circuit-Switched Networks - Bagchi, Amitabha; Chaudhary, Amitabh; Scheideler, Christian; Kolman, Petr (SIAM J. Discrete Math.)

Linearization: Locally Self-Stabilizing Sorting in Graphs - Onus, Melih; W. Richa, Andrea; Scheideler, Christian (Proceedings of the Nine Workshop on Algorithm Engineering and Experiments, ALENEX 2007, New Orleans, Louisiana, USA, January 6, 2007)

Towards Scalable and Robust Overlay Networks - Awerbuch, Baruch; Scheideler, Christian (6th International workshop on Peer-To-Peer Systems, IPTPS 2007, Bellevue, WA, USA, February 26-27, 2007)

A denial-of-service resistant DHT - Awerbuch, Baruch; Scheideler, Christian (Proceedings of the Twenty-Sixth Annual ACM Symposium on Principles of Distributed Computing, PODC 2007, Portland, Oregon, USA, August 12-15, 2007)

A Denial-of-Service Resistant DHT - Awerbuch, Baruch; Scheideler, Christian (Distributed Computing, 21st International Symposium, DISC 2007, Lemesos, Cyprus, September 24-26, 2007, Proceedings)

Distributed Computing in Sensor Systems, Third IEEE International Conference, DCOSS 2007, Santa Fe, NM, USA, June 18-20, 2007, Proceedings

SPAA 2007: Proceedings of the 19th Annual ACM Symposium on Parallelism in Algorithms and Architectures, San Diego, California, USA, June 9-11, 2007

Overlay Networks for Peer-to-Peer Networks - W. Richa, Andrea; Scheideler, Christian (Handbook of Approximation Algorithms and Metaheuristics.)

Dynamic and redundant data placement - Brinkmann, André; Effert, Sascha; Meyer auf der Heide, Friedhelm; Scheideler, Christian (IEEE International Conference on Distributed Computing Systems (ICDCS))
We present a randomized block-level storage virtualization for arbitrary heterogeneous storage systems that can distribute data in a fair and redundant way and can adapt this distribution in an efficient way as storage devices enter or leave the system. More precisely, our virtualization strategies can distribute a set of data blocks among a set of storage devices of arbitrary non-uniform capacities so that a storage device representing x% of the capacity in the system will get x% of the data (as long as this is in principle possible) and the different copies of each data block are stored so that no two copies of a data block are located in the same device. Achieving these two properties is not easy, and no virtualization strategy has been presented so far that has been formally shown to satisfy fairness and redundancy while being time- and space-eflcient and allowing an efficient adaptation to a changing set of devices.

Can ISPs and P2P users cooperate for improved performance? - Aggarwal, Vinay; Feldmann, Anja; Scheideler, Christian (ACM Computer Commucation Review)

Improved bounds for the unsplittable flow problem - Kolman, Petr; Scheideler, Christian (J. Algorithms)

Survivable Monitoring in Dynamic Networks - Ateniese, Giuseppe; Riley, Chris; Scheideler, Christian (IEEE Trans. Mob. Comput.)

Distributed coloring in O/spl tilde/(/spl radic/(log n)) bit rounds - Kothapalli, Kishore; Scheideler, Christian; Onus, Melih; Schindelhauer, Christian (IPDPS)

Robust Random Number Generation for Peer-to-Peer Systems - Awerbuch, Baruch; Scheideler, Christian (OPODIS)

Towards a scalable and robust DHT - Awerbuch, Baruch; Scheideler, Christian (SPAA)

The Effect of Faults on Network Expansion - Bagchi, Amitabha; Bhargava, Ankur; Chaudhary, Amitabh; Eppstein, David; Scheideler, Christian (Theory Comput. Syst.)

Towards a paradigm for robust distributed algorithms and data structures - Scheideler, Christian (6th International HNI Symposium on New Trends in Parallel and Distributed Computing)

Transparent Data Structures, or How to Make Search Trees Robust in a Distributed Environment - Korzeniowski, Miroslaw; Scheideler, Christian (ISPAN)

Supervised Peer-to-Peer Systems - Kothapalli, Kishore; Scheideler, Christian (ISPAN)

Efficient Broadcasting and Gathering in Wireless Ad-Hoc Networks - Onus, Melih; W. Richa, Andrea; Kothapalli, Kishore; Scheideler, Christian (ISPAN)

Constant density spanners for wireless ad-hoc networks - Kothapalli, Kishore; Scheideler, Christian; Onus, Melih; W. Richa, Andrea (SPAA)

How to spread adversarial nodes?: rotate! - Scheideler, Christian (STOC)

Overlay networks for wireless ad hoc networks - Scheideler, Christian (IMA Workshop on Wireless Communications)

Simple On-Line Algorithms for the Maximum Disjoint Paths Problem - Kolman, Petr; Scheideler, Christian (Algorithmica)

Group Spreading: A Protocol for Provably Secure Distributed Name Service - Awerbuch, Baruch; Scheideler, Christian (ICALP)